Turmeric trends: analyzing consumer preferences and willingness to pay - Nguyen, Ly; Govindasamy, Ramu; Mentreddy, Srinivasa R. (Frontiers in Sustainable Food Systems, 2024)
This Research determines the factors influencing American consumers’ willingness to purchase turmeric products, amidst the spice’s rising popularity for its potential health benefits, particularly those linked to its bioactive component, curcumin. Through a comprehensive analysis of a Qualtrics online survey with 1,020 national respondents in the U.S., we employed advanced choice experiment mixed logit models to elucidate consumer preferences regarding product form, origin, sustainability certification, curcumin content, and price. Contrary to the initial hypothesis that curcumin potency would be a primary driver, our results indicate that the place of origin and price significantly shape purchasing decisions, with a clear preference for inland domestically grown, organically certified turmeric products. These insights offer valuable guidance for producers, manufacturers, and marketers in the natural products industry, suggesting a focus on emphasizing local, sustainable sourcing and clear communication of organic credentials to align with consumer expectations. Our findings not only provide a detailed understanding of current consumer attitudes toward turmeric but also highlight potential markets for turmeric–based product development and effective marketing to cater to the evolving demand for health-beneficial natural products.